Effects of radiofrequency on the healing of skin wounds in rats: analysis using digital planigraphy and histological evaluation - Ana Maria Cardoso Cepeda; Antonio Carlos Campos; Gilian Fernanda Dias Erzinger; Priscila Balbinot (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Given the extensive use of plastic surgery and the search for better aesthetic and functional results, it is necessary to research ways to improve healing and scarring. The objective is to evaluate the effects of three radiofrequency (RF) sessions in healing the skin of mice. METHODS: Forty-eight rats were divided into four groups by day of sacrifice and treatment (RF group: RG; control group: CG). Dissection of the excisional wound of 2 cm x 2 cm (4 cm²) was performed and a 6-mm punch was used to hold two excisional wounds 0.6 cm in diameter. After 24 h, radiofrequency was performed using Spectra® directly on the wound in the dorsal region for 7 minutes at 38ºC. This was repeated three times on alternate days. For the control group, the radiofrequency protocol was performed with the device switched off. RESULTS: A larger area of the square wound was measured on postoperative day three in RG (RG7: 3.3 cm² ± 0.7 cm² vs. CG7: 2.4 cm² ± 0.4 cm²; p = 0.009). On day 14, the square wound in RG was greater than in CG (RG14: 1.9 cm² ± 0.5 cm² vs. CG14: 1.0 cm² ± 0.3 cm²; p = 0.001). There was a 90% closure of wounds in CG14. In RG14, 60% of the wounds were re-epithelized while 40% remained ulcerated. In CG7, 70% of the remaining wounds were ulcerated and 30% were re-epithelized. In RG7, 8% were re-epithelized and 92% remained ulcerated. CONCLUSION: Radiofrequency has a negative influence on the healing process, as indicated by mice that received radiofrequency having a persistent ulcerated wound.